Implementación de un aplicativo móvil sobre la lectura de códigos QR para llevar información de la trazabilidad sobre la comercialización y exportación de banano en la Agrícola Bananera y Exportadora 2 Hermanos. - Calle Morales, Genesis Gabriela (2022)
In Ecuador there are currently a large number of banana agricultural companies which have a good infrastructure and administration capable of generating very high productions with good quality for export, but they do not have a technology that allows users to access information on traceability. of the product quickly, safely and reliably. The purpose of this research project is to provide consumers with access to information on the traceability of bananas through the implementation of a mobile application on the reading of QR codes and a web application to generate the codes with the information required on the process. of the banana, such as the hacienda or farm where it is harvested, the owner of the farm that processes the banana, the date of the shipment process, the lot from which the banana comes, the hygiene of the banana (technical sheet of the product) and what was the exporter in charge of the commercialization in such a way that the beneficiaries such as the producers, the exporter, the wholesalers and the consumers will have access to said information when required. The project was executed by applying the Scrum development methodology with innovative development technologies preselected in the research path, such as the Ionic and Angular framework, both of JavaScript used for the development of the mobile application and the Electron framework for the development of the web application. , the data will be stored in the MySQL DB, resulting in the mobile application that displays the information of the QR code and the web application that generates said QR codes.